Crotalus durissus cascavella venom toxicity to mammalian cells - Araújo, Lucelina da Silva (2016)
Snakes from the genus Crotalus gained significant space in the scientific field since the development of researches with their venom involving cytotoxic activity. Crotalus durissus cascavella is the only subspecies recorded of the Caatinga biome of Northeastern Brazil and it’s noticed a lack of studies on its venom properties. The present study evaluated the crude venom of C. d. cascavella for its cytotoxic activity in vitro against both tumor cell lines and normal cells. The mechanism of cell death induced by this venom was also investigated. C. d. cascavella venom presented high cytotoxicity (IC50 values ranging from 2.7 to 6.9 μg/mL) against five tumor cells lines: OVCAR-8 and SKOV3 (ovarian carcinomas), PC-3M (metastatic prostate carcinoma), MCF-7 (breast carcinoma), and SF-268 (glioblastoma) and PBMC as well. The cells treated with C. d. cascavella venom triggered the apoptotic pathway as confirmed by several methods. These results underline the biomedical potential of toxins from the venom from this species.